Analisis Implementasi Keselamatan dan Kesehatan Kerja (K3) Petugas Kargo Maskapai Wings Air Oleh PT. Merpati Angkasa Abadi di Bandar Udara Sultan Muhammad Kaharudin Sumbawa - Rizky Aldi Pratama; Febriansyah Ignas Pradana (CV. Aksara Global Akademia, 2023)
This study aims to find out how the implementation of occupational safety and health (K3) for Wings Air airline cargo officers by PT. Merpati Angkasa Abadi at Sultan Muhammad Kaharudin Airport, Sumbawa and to find out how efforts to maintain the implementation of occupational safety and health (K3) for Wings Air airline cargo officers by PT. Merpati Angkasa Abadi at Sultan Muhammad Kaharudin Airport, Sumbawa The research design uses a qualitative research approach, namely research used to examine the condition of scientific objects where a researcher is the key instrument. From the results of the research that the author has done, that is, every company, especially those with high-risk interactions, must have a standard operating procedure (SOP), and every officer must receive monitoring at work to use personal protective equipment (PPE) in accordance with the procedure, then from the level of awareness of each Each officer already has an awareness of the risks of their work and every time they start or when they are finished, a briefing is carried out to remind them of the risks and hazards at work. and in an effort to maintain the implementation of OSH, training is usually carried out once a year, then for steps to anticipate hazards, officers usually double-check before and after use, and for each officer to have concern for work risks, for example, by reminding one another the other at work.